Math Modeling of Vacuum Conductive Timber Drying; Advanced Materials Research; Vol. 1040 : High Technology: Research and Applications 2014 (HTRA 2014) - Goreshnev M. A. Maksim Alekseevich (2014, 2014)
Title screen